(untitled) (Research, Society and Development, 2024)
The present work aims to investigate the possibility of using programming languages to improve mathematics learning, based on the application of programming resources to solve mathematical problems, influenced by students’ personal repertoires, interactions and collaborations with the work team. Problems adapted from the Brazilian Informatics Olympiads, applied in previous years, were used for resolution in the languages ​​C++, Java, JavaScript and Python, at the discretion of the participants. The solution strategy applied, as well as the use or not of external materials for consultation, was free choice, being encouraged collaboration between students and the use of more than one programming language to solve each problem. In the end, two problems were chosen for quantitative analysis, based on the metrics number of lines of code, execution time and number of calls to functions in the source code. A qualitative analysis of the problem-solving process was also carried out. The use of different strategies to solve problems was observed, mainly influenced by students’ previous experiences and resources specific to the available languages. An increase in the level of programming and problem-solving skills and an improvement in the perception of one’s own skills in both areas were noted.